Another Hardy-Hilbert’s Integral Inequality - Sulaiman, W. T. (Sarajevo Journal of Mathematics, 2024)
We give a new kind of Hardy-Hilbert integral inequality via homogeneous functions as well as some other generalizations. Special cases are also obtained. 2000 Mathematics Subject Classification. 26D15